Methods of registrar post allocation - Ramchandani, P; Sayal, K; Kapur, N (1997)
Little is known about how posts are allocated to enable individuals to experience a comprehensive pre-membership psychiatric training. A questionnaire survey of 26 teaching hospital training schemes was carried out. This concentrated on registrar training - post-Part 1 MRCPsych (now known as senior house officers since the Calman changes). Four main methods of allocation, with varying degrees of trainee involvement, were identified. The amount of prior notice given of the trainees' next placement and perceived advantages and disadvantages were compared between the lour methods. Implications for practice are discussed.